Enabling Fast Pseudo‐2D NMR Spectral Acquisition for Broadband Homonuclear Decoupling: The EXACT NMR Approach. Issue 15 (8th June 2017) - Ndukwe, Ikenna E.; Shchukina, Alexandra; Zorin, Vadim; Cobas, Carlos; Kazimierczuk, Krzysztof; Butts, Craig P.
Abstract: Pseudo‐2D NMR spectroscopy provides a means of acquiring broadband homonuclear decoupled spectra useful for structural characterization of complex molecules. However, data points concatenated in the direct dimension in these experiments are acquired over incremented time periods—leading to long acquisition times with no sensitivity benefits due to the absence of signal averaging between scans. Herein, the concept of EXACT NMR spectroscopy ("burst" non‐uniform sampling of data points) is explored in pseudo‐2D experiments with results revealing little or no loss in spectral quality or signal intensity despite the acceleration of acquisition—up to 400 % in some cases. Abstract : Bringing NMR up to speed : Pseudo‐2D NMR spectroscopy provides a means of acquiring broadband homonuclear decoupled spectra useful for structural characterization of complex molecules. In this work, the concept of EXACT NMR ("burst" non‐uniform sampling of data points) is explored in pseudo‐2D experiments enabling the significantly accelerated acquisition of spectral data with no loss in spectral quality or signal intensity.